Young Adult Carers: The Impact of Caring on Health and Education. (9th December 2018) - Becker, Saul; Sempik, Joe
Abstract : Research has shown that young people who care for parents and relatives (young carers and young adult carers) are at greater risk of mental and emotional difficulties and are more likely to do badly at school or college. To explore the difficulties faced by young adult carers (aged 14–25) in the UK, an online survey was conducted. Almost half (45%) of the 295 respondents reported having a mental health problem. The relationship between the extent of caring and perceived mental health problems and the impact of caring responsibilities on work and education were investigated.